Middle East and North Africa Economic Developments and Prospects 2006 : Financial Markets in a New Age of Oil - World Bank (Washington, DC: World Bank, 2016)
This edtion of the Middle East and North Africa (MENA) economic developments and prospects reports highlights the recent key economic developments as well as the forces underlying the region's economic outcomes. It analyzes the region's medium term growth prospects given global forecasts, and charts the region?s progress with implementing comprehensive structural reforms needed for longer-term growth. For the third year in a row, MENA enjoyed a spectacular year of growth, buoyed by record high growth rates among the region's oil exporters. As oil prices continued their upward climb, the MENA region grew by an average of 6.0 percent over 2005, up from 5.6 percent over 2004, and compared with average growth of only 3.5 percent over the late 1990s. On an annual basis, MENA's average economic growth over the last three years, at 6.2 percent per year, has been the highest three-year growth period for the region since the late 1970s. MENA's regional growth upturn has not been universally shared, however, and resource poor economies are increasingly feeling the adverse impact of higher oil prices. Growth patterns among oil producers, on the other hand, have been increasingly harmonized, reflecting a trend toward common development strategies. Over the medium term, general conditions for maintaining a solid pace for growth appear promising. The oil shock MENA is experiencing has had important financial spillovers. Over the last few years, MENA has seen an upsurge in financial activity, as abundant liquidity has fed a rapid rise in credit growth, surging stock markets, and a booming real estate sector. A troubling aspect about MENA's financial markets is the seeming disconnect between the financial sector and the real private economy, despite the appearance of a relatively deep financial sector by macroeconomic indicators. Along with across the board policy reform, MENA economies continue to look to selective industrial policies designed to enhance specific sector competitiveness and growth to complement more broad-based structural reform. Although the views on industrial policy are changing, and a variety of economic justifications can be made for their use, MENA's own unsuccessful history with industrial policies (and the difficulty in transitioning out of them) should serve as a cautious reminder that the most effective policies for promoting growth rely on strategies to create a neutral and internationally competitive business environment.